Pollen and spores from Lower Cretaceous in Guyang Basin of Inner Mongolia, China and their palaeoclimatic and paleoecological significance. (28th June 2017) - Jin, Peihong; Chen, Jingwei; Wang, Zixi; Xu, Xiaohui; Yang, Guolin; Du, Baoxia; Sun, Bainian
Abstract: Research on the climate and vegetation of the Cretaceous is fundamental to understanding the present environment. The present study focuses on the Lower Cretaceous Guyang Formation (Inner Mongolia), which yields unique macrofossils and diverse palynological assemblages that are used to understand the palaeoecology. In total, 56 genera are identified in the examined assemblage, which are dominated by spores and pollen of pteridophytes and gymnosperms. The gymnosperm pollen is dominated by Taxodiaceae, which belong to Coniferales, and a large proportion of pollen attributable to the Cycadophyta and Ginkgopsida. The pteridophyte spores are dominated by taxa attributable to the Lygodiaceae and Cyatheaceae. Quantitative analysis based on the geographical distribution of modern plant communities and the Sporomorph Ecogroup (SEG) model, the palynomorph associations are used to infer the presence of a closed coniferous forest dominated by Podozamitales, Picea and Podocarpus with understory vegetation comprising ferns prevailed. The fossil palyno flora indicates a warm and humid subtropical climate during Early Cretaceous of Inner Mongolia. Abstract : The present study focuses on the Lower Cretaceous Guyang Formation (Inner Mongolia), which has yielded unique macrofossils and diverse palynological assemblages that are used to understand the palaeoecology. In total, 56 genera were identified in the examined assemblage, and they are dominated by pteridophytes and gymnosperms. According to a quantitative analysis based on the geographical distribution of modern plant communities and the Sporomorph Ecogroup (SEG) model, the fossil flora indicate a warm and humid subtropical climate during this period. Abstract : 白亜紀の気候と植生の研究は現在の環境を理解する上で重要である.  本研究では,   古生態の理解に有用な,   独特な大型化石と多様な花粉・胞子群を産する内モンゴルの下部白亜系グヤン(Guyang)層に焦点をあてる.  研究対象とした花粉・胞子群から総計56属が同定され,   それらは球果植物門に属するスギ科が卓越し,   さらにソテツ類や,   イチョウ類も多い.  シダ類はカニクサ科やヘゴ科が卓越する.  現生植物群集の地理的分布や胞子形態生態群(SEG)モデルに基づいた定量的分析によれば,   この植物群はポドザミテス類,   トウヒ属,   マキ属の卓越する針葉樹林の存在を示しており,   それらのグループに加えて,   シダ類やその他のシダ植物門からなる密生する草冠および下層植生を伴い,   湖成淡水藻類も含んでいたことを示唆している.  この化石植物群はその当時,   温暖湿潤な亜熱帯気候にあったことを示している.